2012
DOI: 10.4081/or.2012.e25
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical outcome and complications related to balloon kyphoplasty

Abstract: The treatment of painful osteoporotic vertebral compression fractures using transpedicular cement augmentation has grown significantly over the last two decades. The benefits of balloon kyphoplasty compared to conservative treatment remain controversial and are discussed in the literature. The complication rates of vertebroplasty and kyphoplasty are considered to be low. The focus of this study was the analysis of acute and clinically relevant complications related to this procedure. In our department, all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
1
8
1
Order By: Relevance
“…Within following 11 months the mean ODI ranged between 16% and 10%, signifying minimal disability. Aforementioned results are confirmed in literature [3,6,7,15,16]. However, in our study clinical outcome shows discrepancy with radiological results: reduction of LK was achieved in 51.7% of vertebrae, it succeeded in 66.7% of patients; amongst them only 37.5% had the kyphosis of all fractured vertebrae reduced.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Within following 11 months the mean ODI ranged between 16% and 10%, signifying minimal disability. Aforementioned results are confirmed in literature [3,6,7,15,16]. However, in our study clinical outcome shows discrepancy with radiological results: reduction of LK was achieved in 51.7% of vertebrae, it succeeded in 66.7% of patients; amongst them only 37.5% had the kyphosis of all fractured vertebrae reduced.…”
Section: Discussionsupporting
confidence: 69%
“…In the next step, the created void is filled with injectable bone cement, most commonly polymethylmethacrylate (PMMA), which consecutively hardens stabilizing the shape of expanded vertebra [1,2,4,5]. After more than a decade of experience, the clinical benefits as well as radiographical results of BKP remain debated [4,[6][7][8][9][10][11][12][13][14][15][16]. The objective of this study was to analyse the effects of BKP on correction of local kyphosis, pain relief and patient's quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…48 Kyphoplasty is most successful at restoring the height of the fractured vertebral body if it is performed within 3 months of the occurence of fracture or onset of pain. 22,23,43,49,50 Short-term results show that 85% to 100% of patients have good to moderate pain relief. 26, 48 Wardlaw et al found that kyphoplasty had improved functional recovery compared with nonsurgical treatment.…”
Section: Operative Managementmentioning
confidence: 99%
“…Furthermore, fractures of the 5 th lumbar vertebra are quite uncommon, representing only 1.2% of overall spine fractures and 2.2% of thoraco-lumbar fractures9). On the other hand, according to the previous studies on percutaneous vertebroplasty (PVP) or kyphoplasty, the incidence of PVP at L3, L4 and L5 is about 9-13%, 5-9% and 2-5% respectively of all their thoraco-lumbar PVP or kyphoplasty procedures5,18,21,28,29). Therefore, the approximate incidence of PVP at L3 is near to the sum of incidence of PVP at L4 or L5.…”
Section: Introductionmentioning
confidence: 99%